2021
DOI: 10.1007/s10639-021-10714-w
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating (dis-)engagement in K-12 blended learning

Abstract: It is well-recognised that engagement is critical for learning and school success. Engagement (and disengagement) are, however, also influenced by context. Thus, as digital technologies add complexity to the educational context, they influence classroom leadership, lesson designs and related practices, and thereby engagement. Despite being critical, engagement and disengagement are not well explored concerning these influences, with a lack of research undertaken within socially disadvantaged schools. In this q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 84 publications
2
15
1
Order By: Relevance
“…Their results showed that students’ engagement was a fundamental factor to generate positive and internalised attitudes of the positive effect of attending classes. In this line, additional practice and better outcomes have been found in previous literature (Bergdahl & Bond, 2022 ). Thus, in accordance with control-value theory and previous research, the following hypothesis is formulated: H3: The greater students’ participation in CGOL is, the better students’ class-related emotions are.…”
Section: Literature Reviewsupporting
confidence: 67%
“…Their results showed that students’ engagement was a fundamental factor to generate positive and internalised attitudes of the positive effect of attending classes. In this line, additional practice and better outcomes have been found in previous literature (Bergdahl & Bond, 2022 ). Thus, in accordance with control-value theory and previous research, the following hypothesis is formulated: H3: The greater students’ participation in CGOL is, the better students’ class-related emotions are.…”
Section: Literature Reviewsupporting
confidence: 67%
“…Kim and Kim [30] reported that the interactions with other students and presence of instructors have a positive effect on student engagement, leading to enhanced students' satisfaction in asynchronous online courses. Bergdahl and Bond [31] and Mutalib et al [32] suggested that the lack of instructor-learner interaction affects the level of student engagement.…”
Section: Student Engagement and Interactionmentioning
confidence: 99%
“…Holistic development, which includes the development of soft skills while engaging in play-based activities to solve problems aligned with learning outcomes, is believed to contribute to feelings of success and happiness (Keung & Cheung 2019, p. 636). On the other hand, recent studies in education report on learners disengaging from and not thriving in pure digital settings (Bergdahl & Bond 2022, p. 2653Gillett-Swan 2017, p. 28).…”
Section: Play-based Learningmentioning
confidence: 99%